2017
DOI: 10.1080/01480545.2017.1410171
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the acute toxicity of chlorpyrifos and cypermethrin toHeteropneustes fossilisand their impact on acetylcholinesterase activity

Abstract: In the present study, the acute toxicity of chlorpyrifos (an organophosphate, OP) and cypermethrin (a pyrethroid) pesticides was estimated for 96 h in Heteropneustes fossilis. The LC for chlorpyrifos (CPF) and cypermethrin was found to be 1.90 mg/L and 0.085 mg/L, respectively. The acetylcholinesterase (AChE, EC 3.1.1.7) activity in Heteropneustes fossilis exposed to both the insecticides was assayed in brain, muscle and gills. In general, tissue specific as well as dose-dependent decrease in the AChE activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In the present study, two groups of pesticides namely chlorpyrifos (50%) [O, O-diethyl O-3, 5, 6-trichlor- 2-pyridyl phosphorothioate; CPF; PubChem CID: 2730] (an organophosphate; OP) and cypermethrin (5%) [RS-cyano (3 phenoxybenzyl) (1RS)-cis, trans-3–(2,2-dichlorovinyl)- 2,2-dimethylcyclopropane carboxylate; PubChem CID: 2912] (a pyrethroid) and their combination [chlorpyrifos (50%) + cypermethrin (5%)] were selected for acute and sub-acute toxicity evaluation in earthworm. Both Chlorpyrifos and cypermethrin are broad-spectrum insecticides used to control agricultural pests and have been listed as pesticides of potential concern by the US National Oceanic and Atmospheric Administration [9,10]. A variety of irreversible/reversible neurobehavioral and neurotoxic effects as well as physiological and morphological alterations have been reported in earthworms even at very low concentration of pesticide [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, two groups of pesticides namely chlorpyrifos (50%) [O, O-diethyl O-3, 5, 6-trichlor- 2-pyridyl phosphorothioate; CPF; PubChem CID: 2730] (an organophosphate; OP) and cypermethrin (5%) [RS-cyano (3 phenoxybenzyl) (1RS)-cis, trans-3–(2,2-dichlorovinyl)- 2,2-dimethylcyclopropane carboxylate; PubChem CID: 2912] (a pyrethroid) and their combination [chlorpyrifos (50%) + cypermethrin (5%)] were selected for acute and sub-acute toxicity evaluation in earthworm. Both Chlorpyrifos and cypermethrin are broad-spectrum insecticides used to control agricultural pests and have been listed as pesticides of potential concern by the US National Oceanic and Atmospheric Administration [9,10]. A variety of irreversible/reversible neurobehavioral and neurotoxic effects as well as physiological and morphological alterations have been reported in earthworms even at very low concentration of pesticide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous report have shown that CP is toxic to the fish by inhibiting brain acetylcholinesterase (AChE) activity (Tiwari et al, 2019). In this study, frozen heads of zebrafish (control and treatment exposure groups) were thawed and homogenized in 0.1M sodium phosphate (NaPO4; pH 7).…”
Section: Biochemical Assays: Apoptosis Acetylcholinesterase Activity ...mentioning
confidence: 99%
“…Even though the fertilizer industry effluent at high concentrations markedly affected the fish organs tested, the magnitude of response varied from the one organ to the other. The decline in AChE activity could be considered as a useful tool for the assessment of industrial effluent toxicity, as it has been the case for other xenobiotic compounds such as organophosphate pesticides and heavy metals (Yadav et al, 2009;Rajkumar and Milton, 2011;Al-Ghais, 2013;Ramesh and Nagarajan, 2016;Tiwari et al, 2017).…”
Section: Acetylcholinesterase Activitymentioning
confidence: 99%
“…In the aquatic ecosystem, fish play crucial role in the monitoring of water contamination as they respond in most sensitivity to variations in aquatic pollution (Naigaga et al, 2011). Stinging catfish H. fossilis (name "stinging" due to its venomous nature) is a native fish species of India and is economically important due to its nutritive and medicinal value (Talwar and Jhingran, 1991;Tiwari et al, 2017). Its body is elongated and depressed towards head region in order to survive in drastic conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%